Implementation and responsiveness of indigenous people education program in Socsargen - Norberte, Norman (Goodwood Publishing, 2024)
Purpose: This study aimed to examine the implementation and responsiveness of the Indigenous Peoples Education Program (IPEd) in South Cotabato, Sarangani, and General Santos City (SocSarGen), focusing on evaluating the level of IPEd implementation and schools' responsiveness in meeting the educational requirements of Indigenous Peoples students enrolled in the IPEd initiative. Research methodology: A descriptive quantitative approach was utilized, employing surveys to gather data on the implementation and responsiveness of the IPEd Program. The data were analyzed to evaluate the degree of implementation and responsiveness of the various indicators. Results: The findings revealed strong implementation of the IPEd Program, emphasizing robust support for building learning resources, ensuring teachers' efficiency, and creating a culturally responsive curriculum. Notable success was observed in curriculum development, learning resources, educational intervention, and the physical learning environment. However, capacity building remains an area of improvement. Limitations: The scope of the study is confined to South Cotabato, Sarangani, and General Santos City, focusing solely on the specific dimensions of IPEd implementation and responsiveness within the specified geographic area. Contribution: This study enhances the existing knowledge base by delivering a thorough evaluation of the implementation and responsiveness of the IPEd Program in SocSarGen. It offers valuable insights to policymakers, educators, and stakeholders to enhance the quality of education for indigenous students and to foster educational equity. Novelty: This study contributes to a comprehensive understanding of the implementation and responsiveness of the IPEd Program in SocSarGen.